The role of catchment characteristics, discharge, and active- layer thaw in seasonal stream chemistry across 10 permafrost catchments - A. Grewal; A. Grewal; E. M. Nicholls; S. K. Carey (Hydrology and Earth System Sciences)
High-latitude catchments are rapidly warming, leading to altered precipitation regimes, widespread permafrost degradation, and shifts in stream chemistry across major arctic rivers. In headwater catchments, seasonal deepening of flow paths due to active-layer thaw and declining discharge post-snowmelt drive variability in stream chemistry during the open-water period. In North American permafrost regions, activation of deeper mineral layers as the season progresses typically increases major-ion concentrations while decreasing dissolved organic carbon (DOC) concentrations. Despite decades of research on seasonality in stream chemistry within permafrost regions, the relative influence of active-layer thaw and discharge remains unresolved. Additionally, the role of permafrost extent and topography in driving seasonality of these solutes is poorly constrained. To address these knowledge gaps, we measured discharge and sampled major-ion and dissolved organic carbon (DOC) concentrations across 10 permafrost catchments in Yukon Territory, Canada. We analyzed concentration–discharge relationships using generalized additive models to resolve the distinct influence of discharge and seasonal active-layer thaw on stream chemistry and to identify the role of watershed characteristics on the magnitude and seasonality of solute concentrations. After accounting for seasonal variations in discharge, we found that both major ions and DOC were highly seasonal across all catchments, with DOC declining and major-ion concentrations increasing post-freshet. Seasonal variability in major-ion concentrations was primarily driven by active-layer thaw, whereas DOC seasonality was strongly influenced by flushing of soil organic carbon during freshet. While average major-ion concentrations were geologically mediated, greater permafrost extent led to enhanced seasonality in concentrations. Catchments with strong topographical gradients and thinner organic soils had higher specific discharge and lower DOC concentrations but greater relative seasonality. Our results highlight the important role catchment characteristics play in shaping the seasonal variations in and magnitude of solute concentrations in permafrost-underlain watersheds.